The Usage of Histamine Type 1 Receptor Antagonist and Risk of Dementia in the Elderly: A Nationwide Cohort Study - Yang, Chuan-Chi; Chien, Wu-Chien; Chung, Chi-Hsiang; Lai, Chung-Yu; Tzeng, Nian-Sheng (Frontiers in Aging Neuroscience, 2022)
Background The histamine type 1 receptor antagonist (H1RA) has been commonly used. This study aimed to examine the association between the usage of H1RA and the risk of dementia. Methods A total of 8,986 H1RA users aged ≥50 and 26,958 controls matched a ratio of 1:3 for age, sex, and comorbidity, were selected between January 1, and December 31, 2000, from Taiwan’s National Health Insurance Research Database. Fine and Gray’s survival analysis (competing with mortality) was used to compare the risk of developing dementia during a 15-year follow-up period (2000–2015). Results In general, the H1RA usage was not significantly associated with dementia (adjusted subdistribution hazard ratio [SHR] = 1.025, 95% confidence interval [CI] = 0.883–1.297, p = 0.274) for the H1RA cohort. However, a differential risk was found among the groups at risk. The patients with the usage of H1RA aged ≥65 years (adjusted SHR: 1.782, 95% CI = 1.368–2.168, p < 0.001) were associated with a higher risk of dementia, in comparison to the control groups. Furthermore, the patients with the usage of H1RA that were male, or had more comorbidities, were also associated with an increased risk of dementia. Conclusion The usage of H1RA was associated with the risk of developing dementia in the patients aged ≥ 65 years.